Temperaturderivate zur strategischen Absicherung von Beschaffungs- und Absatzrisiken - Pierre Chevalier; Thomas Heidorn; Christian Krieger (Hochschule für Bankwirtschaft (HfB), 2003)
Underlyings of weather derivatives in Europe tend to be average temperature compared to heating (cooling) day in the USA because of a smaller volatility in temperature. The derivatives are priced using as burn analysis. Using a gas utility company, hedging techniques are shown using temperature options.
urn:nbn:de:101:1-2008072219
Keywords: 330; Wetterderivate; Risikomanagement; Heating Days Call; Heating Days Put; Average Temperature Collar; Average Temperature Swap; Hedging gas prices with weather derivatives